2019
DOI: 10.3390/cancers11040479
|View full text |Cite
|
Sign up to set email alerts
|

Combined Targeting of Estrogen Receptor Alpha and XPO1 Prevent Akt Activation, Remodel Metabolic Pathways and Induce Autophagy to Overcome Tamoxifen Resistance

Abstract: A majority of breast cancer specific deaths in women with ERα (+) tumors occur due to metastases that are resistant to endocrine therapy. There is a critical need for novel therapeutic approaches to resensitize recurrent ERα (+) tumors to endocrine therapies. The objective of this study was to elucidate mechanisms of improved effectiveness of combined targeting of ERα and the nuclear transport protein XPO1 in overcoming endocrine resistance. Selinexor (SEL), an XPO1 antagonist, has been evaluated in multiple l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…Our RNA-Seq analysis showed that PPARGC1A (PGC1α) mRNA [ 13 ], ( Figure 5 A) was induced by SEL treatment in endocrine resistant cell lines and protein expression of PGC1α was also increased ( Figure 5 B). PGC-1α is a major regulator of mitochondrial biogenesis, and overexpression of this protein was implicated in regulation of glutamine metabolism [ 18 ] and resistance to metabolic drugs [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our RNA-Seq analysis showed that PPARGC1A (PGC1α) mRNA [ 13 ], ( Figure 5 A) was induced by SEL treatment in endocrine resistant cell lines and protein expression of PGC1α was also increased ( Figure 5 B). PGC-1α is a major regulator of mitochondrial biogenesis, and overexpression of this protein was implicated in regulation of glutamine metabolism [ 18 ] and resistance to metabolic drugs [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, we used 6-week-old BALB/c athymic (RRID: IMSR_TAC:balb), ovariectomized, nude female mice from Taconic Biosciences. Power calculations were done based on our previously published studies and five animals per group were used [ 11 , 13 ]. After one week of acclimatization, we injected 1 × 10 6 cells resuspended in 50% PBS and 50% Matrigel subcutaneously into both the right and left flank of each mouse.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations